AMPK Causes Cell Cycle Arrest in LKB1-deficient Cells via Activation of CAMKK2 - Fogarty, Sarah (Mol Cancer Res, 2016)
The AMP-activated protein kinase (AMPK) is activated by phosphorylation at Thr172, either by the tumor suppressor kinase LKB1 or by an alternate pathway involving the Ca(2+)/calmodulin-dependent kinase, CAMKK2. Increases in AMP:ATP and ADP:ATP ratios, signifying energy deficit, promote allosteric activation and net Thr172 phosphorylation mediated by LKB1, so that the LKB1-AMPK pathway acts as an energy sensor. Many tumor cells carry loss-of-function mutations in the STK11 gene encoding LKB1, but LKB1 re-expression in these cells causes cell cycle arrest. Therefore, it was investigated as to whether arrest by LKB1 is caused by activation of AMPK or of one of the AMPK-related kinases, which are also dependent on LKB1 but are not activated by CAMKK2. In three LKB1-null tumor cell lines, treatment with the Ca(2+) ionophore A23187 caused a G1-arrest that correlated with AMPK activation and Thr172 phosphorylation. In G361 cells, expression of a truncated, CAMKK2 mutant also caused G1-arrest similar to that caused by expression of LKB1, while expression of a dominant negative AMPK mutant, or a double knockout of both AMPK-α subunits, also prevented the cell cycle arrest caused by A23187. These mechanistic findings confirm that AMPK activation triggers cell cycle arrest, and also suggest that the rapid proliferation of LKB1-null tumor cells is due to lack of the restraining influence of AMPK. However, cell cycle arrest can be restored by re-expressing LKB1 or a constitutively active CAMKK2, or by pharmacological agents that increase intracellular Ca(2+) and thus activate endogenous CAMKK2. IMPLICATIONS: Evidence here reveals that the rapid growth and proliferation of cancer cells lacking the tumor suppressor LKB1 is due to reduced activity of AMPK, and suggests a therapeutic approach by which this block might be circumvented.